2006
DOI: 10.1080/10408390500295490
|View full text |Cite
|
Sign up to set email alerts
|

Food Contamination with Organic Materials in Perspective: Packaging Materials as the Largest and Least Controlled Source? A View Focusing on the European Situation

Abstract: The comparison of the various sources of food contamination with organic chemicals suggests that in the public, but also among experts, the perception of risk is often distorted. Firstly, neither pesticides nor environmental pollutants contribute the most; the amount of material migrating from food packaging into food may well be 100 times higher. Secondly, control of these large migrants is often lagging behind the standards set up for other sources, since many of the components (particularly those not being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 17 publications
0
69
0
1
Order By: Relevance
“…Maybe as many as 99 out of 100 substances turn out to be no relevant problem, but they all must be investigated to identify the one relevant risk. Since foodpackaging materials alone release many 10 000 substances into food [4], even an assumed risk of merely 1% suggests that many substances damage our health.…”
Section: Koni Grobmentioning
confidence: 99%
“…Maybe as many as 99 out of 100 substances turn out to be no relevant problem, but they all must be investigated to identify the one relevant risk. Since foodpackaging materials alone release many 10 000 substances into food [4], even an assumed risk of merely 1% suggests that many substances damage our health.…”
Section: Koni Grobmentioning
confidence: 99%
“…This widespread use results in a ubiquitous distribution of phthalates in the general environment as well as in unwrought food materials [1][2][3]. Additional contamination may then occur during production, processing, and packaging of food [4]. Typical food contact materials that may release phthalates into foodstuffs are plasticized PVC, nitrocellulose, or synthetic rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…Several food crises have confirmed that FCM substances can migrate into food and drinks, subsequently causing unwanted exposure of the consumer to potentially harmful substances (European Commission 2016; EFSA 2011). As a result, health concerns have been raised which are justified especially since migration from FCM is estimated to be the main source of food contamination, quantitatively exceeding most others-including pesticide residues-by a factor of 100-1000 (Grob et al 2006).…”
mentioning
confidence: 99%